Development and radical uncertainty. Issue 8 (16th November 2020) - Feinstein, Osvaldo
ABSTRACT: Development strategies, programmes and projects are designed making assumptions concerning several variables such as future prices of outputs and inputs, exchange rates and productivity growth. However, knowledge about the future is limited. Uncertainty prevails. The usual approach to deal with uncertainty is to reduce it to risk. Uncertainty is perceived as a negative factor that should and can be eliminated. This article presents an alternative approach which recognises that radical uncertainty is irreducible to risk, identifying a positive dimension of uncertainty and showing its implications for development practice.